Rooting the Value System in Educational Institutions to Confront Intellectual Extremism - Tawfiq, Asst. Prof. Dr. Bashair Mawlood Tawfiq; Salman, Prof. Dr. Huda Mohammed Salman (Sulaimani Journal for Humanities, 2026)
Values are considered a fundamental basis for achieving progress and development in societies, as they contribute to building the foundations of peaceful coexistence and cooperation among individuals. Education plays a pivotal role in instilling values in individuals, as it defines the philosophy and educational goals of society, guiding the process of teaching, and developing behaviors and skills.Educational institutions, especially schools, represent a crucial factor in shaping the moral values of individuals by teaching students ethical principles and virtues and providing a learning environment that encourages dialogue and exchange of opinions, thus enhancing positive behaviors.Historically, schools have fulfilled multiple educational and social functions, and these functions have expanded to include more specialized aspects. Although some other institutions share these tasks, the school remains one of the most important contributors to building and reinforcing moral values. The school is a fundamental pillar in constructing and strengthening ethical values, playing an important role in shaping students’ personalities and guiding their behaviors within society. These values are considered a foundation that should be instilled in the minds of children and youth to achieve social stability and eliminate chaos.Studies indicate that educational institutions contribute to reinforcing moral values through the live models they present and positive interactions with students. Schools also help build students’ personalities through daily school relationships, where they learn cooperation, discipline, and ethical conflict resolution. Educational institutions thus form a key pillar in promoting moral values by educating generations in virtues and social values, which contributes to building a stable and advanced society.This research addressed three main themes: (1) the relationship between values and extremism, (2) the impact of education on shaping social values, and (3) the preventive role of education in confronting extremism.
Keywords: value system; educational institutions; intellectual extremism; social values